The Quality of Newborn Data: Assessment of Data Management and Reporting System - Emmanuel Kusi Achampong; Godwin Adzakpah; Richard Okyere Boadu; Obed Owumbornyi Lasim (Intelektual Pustaka Media Utama, 2018)
Data quality assurance through the district, regional and national health information systems is a sure way of having a meaningful interpretation, but this is a challenge in many developing countries. The purpose of this study was to determine the availability and data completeness of key newborn data indicators collected at the health facilities and to determine the use of newborn data for planning and decision-making at the Cape Coast metropolis. The study was a descriptive qualitative assessment. An in-depth interview was conducted in four hospitals within the Cape Coast Metropolis. There were unique best practices identified with some hospitals such as staff distribution and utilization in data collection and reporting, using data for decision making, and to define newborn indicators, data collections tools and the processes involved in data management and utilising supportive supervision from both the region and district levels. In order to sustain health information management, fundamental monitoring and evaluation issues, standardisation of monitoring and evaluation practices in data and information management must be addressed. In addition, investment should be made into the adoption of electronic medical records systems and tertiary training programs to support monitoring and evaluation activities in the hospital.